COMMUNITY PREPAREDNESS FOR FLOOD DISASTERS IN MELIAU SUB-DISTRICT SANGGAU DISTRICT - Bawono, Hari; Tampubolon, Budiman; Anasi, Putri Tipa (Universitas Tanjungpura, 2024)
This research is entitled Community Preparedness for Flood Disasters in Meliau District, Sanggau Regency. The phenomenon of flooding often hits a watershed area that is unable to accommodate the rainwater that falls because the amount of rainwater exceeds the capacity of the river itself. Kuala Buayan Village which is one of the villages in Meliau District is the village most frequently affected by floods almost every year. This has disrupted community activities in Kuala Buayan Village. The purpose of this study is to determine community preparedness for flood disasters. This study uses qualitative methods with descriptive analysis. The data source for this research is the results of interviews with the village government, the Sanggau Regency Regional Disaster Mitigation Agency, and the Kuala Buayan Village Community as well as direct field observations. The results show that knowledge of community preparedness for floods is still lacking. This is based on the Emergency Response Plan, Disaster Warning System, and Mobilization of Community Resources which is still very lacking, considering that Kuala Buayan Village is a Flood-Prone Area. In addition, the community's knowledge about flood disaster preparedness is quite good, but there is still some knowledge and insight that the community needs to know about flood disaster preparedness.